Postgrowth Imaginaries : New Ecologies and Counterhegemonic Culture in Post-2008 Spain. - Prádanos, Luis I. (Contemporary Hispanic and Lusophone Cultures Series, 2019)
Postgrowth Imaginaries brings together environmental cultural studies and postgrowth economics to examine radical cultural shifts sparked by the global financial crisis. The globalization of an economic culture addicted to constant growth destroys the ecological planetary systems while failing to fulfil its social promises. A transition toward what Prádanos calls 'postgrowth imaginaries'--the counterhegemonic cultural sensibilities that are challenging the growth paradigm--is well underway in the Iberian Peninsula today.